2014
DOI: 10.1038/jcbfm.2014.125
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Vascular Leak in a Mouse Model of Amyloid Neuropathology

Abstract: In Alzheimer's disease (AD), there is increasing evidence of blood-brain barrier (BBB) compromise, usually observed as 'microbleeds' correlated with amyloid plaque deposition and apoE-e4 status, raising the possibility of nanotherapeutic delivery. Molecular probes have been used to study neurovascular leak, but this approach does not adequately estimate vascular permeability of nanoparticles. We therefore characterized cerebrovascular leaks in live APP þ transgenic animals using a long circulating B100 nm nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
(45 reference statements)
0
19
0
Order By: Relevance
“…Most microbleeds in EFAD mice were co-localized within Aβ deposits, also seen in another FAD model by dye-visualization of blood leaks (Tanifum et al, 2014). The correlations of microbleed numbers and of the CAA load with human Aβ suggest that increased Aβ levels drive cerebrovascular degeneration with blood-brain barrier (BBB) leakage.…”
Section: Discussionmentioning
confidence: 64%
“…Most microbleeds in EFAD mice were co-localized within Aβ deposits, also seen in another FAD model by dye-visualization of blood leaks (Tanifum et al, 2014). The correlations of microbleed numbers and of the CAA load with human Aβ suggest that increased Aβ levels drive cerebrovascular degeneration with blood-brain barrier (BBB) leakage.…”
Section: Discussionmentioning
confidence: 64%
“…For quantitative analysis of CT images, CT signal was converted into iodine concentration using a normalization factor as per methods described previously [15,16]. The normalization factor was determined by the slope of the line that best fit the plot of CT signal and iodine concentration in the phantom series.…”
Section: Methodsmentioning
confidence: 99%
“…Animal studies using neuropathology, imaging and staining have provided evidence for BBB impairment both in transgenic mouse models of β-amyloidosis [31,32,[143][144][145], and tauopathy [146]. Moreover, these studies have shown that BBB impairment occurs early during disease progression, before onset of Aβ deposition, CAA and cognitive impairment [145].…”
Section: Vascular Integrity In Ad: the Failing Shieldmentioning
confidence: 99%